Genetic resources of tropical forest trees - conservation options - Ahmad, Abdul Manap (Malaysian Nature Society, 1979)

(untitled)
The impact of the activities of conservation of natural resources has been felt in many developing tropical countries. The point has now been reached where conflicts between utilization of the natural resources and the need to conserve for the future supply of these resources have become issues for intense debate. Justifications and options for the conservation of the genetic resources for tropical forest trees are discussed. Biological, economical and ethical reasons are cited and in situ and off site efforts are highlighted.